Precise coupling of the thalamic head-direction system to hippocampal ripples - Guillaume Viejo (Nature Portfolio, 2020)
Thalamic head direction (HD) cells are necessary to establish spatial maps in the hippocampus. Here, the authors show that HD cells tuned to a particular direction are coupled to individual hippocampal ripple events during sleep, suggesting an influence of the replay of specific trajectories during sleep memory consolidation.